Early evaluation of cocoa (Theobroma cacao L.) clones as intercrop in coconut gardens under red river region of Assam State, India - Phukon, R. M.; Nath, J. C.; Sumitha, S.; Maheswarappa, H. P.; Apshara, Elain (Journal of Plantation Crops, 2021)
A field experiment was conducted at Horticultural Research Station (AICRP on Palms), Kahikuchi of Assam Agricultural University for three consecutive years (2018-20) to study the initial performance of cocoa clones as intercrop in adult coconut (Cocos nucifera L) garden spaced at 7.5 m × 7.5 m taking sixteen cocoa clones. Data on tree height, stem girth, number of pods, pod weight, number of beans pod-1, dry bean weight tree-1 year-1 and single dry bean weight revealed significant variations among the 16 cocoa clones. Dried beans are the prime economic produce of cocoa, and single dry bean weight ranged from 0.95 to 1.4 g. With respect to dry bean yield tree-1, VTLC-20 recorded a significantly higher dry bean yield of 2.2 kg tree-1 followed by VTLC-18 (1.5 kg tree-1) compared to other cocoa clones, and eight clones yielded more than 1.0 kg dry bean tree-1. Results showed that the number of leaves on the crown, number of inflorescences per palm and nut yield of coconut was not negatively affected; rather, there was an increase in the yield of coconut over a period.